1996
DOI: 10.1046/j.1365-2125.1996.41420.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient awareness of the adverse effects of non‐steroidal anti‐inflammatory drugs (NSAIDs)

Abstract: We set out to determine the extent to which two groups of patients reported having been informed about the adverse effects of NSAIDs. These consisted of 50 patients who had suffered an acute gastrointestinal bleed while taking a NSAID, and 100 age, sex and drug matched controls who had not. Eight (16%) of the index patients, and 41 (41%) of the control patients remembered having been informed of potential adverse effects, an odds ratio of 3.65 (95% CI 1.55–8.58, P<0.002). Two (4%) of the index patients recalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 5 publications
1
28
0
1
Order By: Relevance
“…In support of a flexible approach to medicine-taking, a study on the use of nonsteroidal anti-inflammatory drugs found that an adaptable approach that involved varying the dose according to the presence of symptoms was less likely to result in hospital admission for upper gastrointestinal bleeding than was rigid compliance to prescribed doses. 200,201 …”
Section: Lay Evaluationmentioning
confidence: 99%
“…In support of a flexible approach to medicine-taking, a study on the use of nonsteroidal anti-inflammatory drugs found that an adaptable approach that involved varying the dose according to the presence of symptoms was less likely to result in hospital admission for upper gastrointestinal bleeding than was rigid compliance to prescribed doses. 200,201 …”
Section: Lay Evaluationmentioning
confidence: 99%
“…3 Several studies have shown that patients who are well informed about side effects have a reduced risk of experiencing serious side effects, because they react when symptoms first show. 8 In addition, well-informed rheumatoid arthritis patients have better symptomatic control with less pain and a higher overall quality of care. 3 This suggests that patient education is a central issue in NSAID treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is important considering that approximately one third of all ulcer bleeding in older people is attributed to NSAIDs (Haslock, 1990). Herxheimer (1998) suggests 'uncomprehending adherence' is potentially dangerous citing Wynne and Long (1996). They i nterviewed 50 c onsecutive patients (experimental group: EG) taking four commonly used NSAIDs who had been admitted to hospital with a gastrointestinal bleed.…”
Section: Uncomprehending Adherencementioning
confidence: 99%